THE USE OF ANDROID-BASED EDUCATIONAL GAMES USING ARTICULATE STORYLINE 3 IN SCIENCE LEARNING DURING A PANDEMIC - Arya Wisata Fitri (Yayasan Citra Dharma Cindekia, 2022)
This research aims to describe (1) the use of android-based educational games using the articulate storyline 3 application in science learning during the pandemic, (2) the learning experiences gained by students by using android-based educational games in science learning during the pandemics. This research used a qualitative descriptive research design. The subjects of this research were science teachers and students of class VII.1 MTsN 4 Pasaman . The object of this research is the use of android-based educational games using the articulate storyline 3 application in science learning. The data collection method used is the method of observation, interviews, and documentation. The results of this study are (1) the use of android-based educational games in science learning, first the students are in the learning process in the classroom, the teacher sends the game to all students in apk format, students install the application on their respective androids according to the teacher's direction, all students learn the material of elements, compounds, and mixtures in applications and take quizzes, (2) the learning experience gained by students by using android-based educational games, which makes it easier for students to understand the material of elements, compounds, and mixtures in learning, making learning more interesting, effective and efficient, motivating students in the learning process, and students' difficulties because some people don't have androids and have to join other students.